Notoginsenoside R1 alleviates the inflammation of osteoarthritis by activating the Nrf2/HO-1 signalling pathway in vitro and in vivo. (October 2021) - Chen, Ming; Zhou, Siqi; Liu, Liang; Wen, Yinxian; Chen, Liaobin
Graphical abstract: Highlights: Inflammation plays a vital role in the progression of osteoarthritis. Notoginsenoside R1 reduces IL-1β-induced inflammation and ameliorate osteoarthritis progression. Nrf/HO-1 signaling pathway is activated in the treatment of Notoginsenoside R1. Abstract: Osteoarthritis (OA) is a major articular degenerative disease characterized by local chronic inflammation and cartilage degeneration. Notoginsenoside R1 (NR1) is one of the bioactive compounds of Panax notoginseng with multiple pharmacological activities. In this study, we investigated the protective effect of NR1 on OA. Rat primary chondrocytes were treated with 10 ng/ml interleukin (IL)-1β to induce an OA-like phenotype in vitro followed by treatment with NR1. The results showed that the IL-1β-induced increased expression of tumor necrosis factor (TNF)-α, IL-6, and inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) was inhibited by NR1. In addition, NR1 downregulated the expression of matrix degrading enzymes and alleviated the degradation of extracellular matrix (ECM). Moreover, activation of the nuclear factor-erythroid 2-related factor-2 (Nrf2)/heme oxygenase-1 (HO-1) signaling pathway was observed after NR1 treatment, which further inhibited the IL-1β-induced activation of the nuclear factor-κB (NF-κB) pathway. Knee OA was induced in rats in vivo by anterior cruciate ligament transaction (ACLT), and NR1 was then administered to rats by gavage. The results revealed that NR1 reduced cartilage degeneration and OA scores of the knee. In conclusion, the present study indicated that NR1 alleviates the inflammation of osteoarthritis by activating the Nrf2/HO-1 signaling pathway, indicating that NR1 may be a potential drug for OA therapy.